Controlabilidade de algumas EDPs não lineares, e, densidade e espectro de subvariedades mínimas em espaço forma. - Vieira, Franciane de Brito (2017)
In the first part of this thesis we deal with the 3D Navier-Stokes and Boussinesq systems in a cube. We prove some results concerning the global approximate controllability by means of boundary controls which act in some part of the boundary. They are generalizations and variants of some previous results by Guerrero, Imanuvilov and Puel. Still in the first part of this Thesis, we prove the internal and boundary local null controllability of a 1D parabolic PDE with nonlinear diffusion. Here, the main tools are Liusternik’s inverse function Theorem and appropriate Carleman estimates. In the second part of this Thesis, we consider M m minimal properly immersed submanifolds in a complete ambient space N n suitably close to a space form N n k of curvature −k ≤ 0. We are interested in the relation between the density function Θ(r) of M m and the spectrum of the Laplace-Beltrami operator. In particular, we prove that if Θ(r) has subexponential growth (when k < 0) or sub-polynomial growth (k = 0) along a sequence, then the spectrum of M m is the same as that of the space form N m k . Notably, the result applies to Anderson’s (smooth) solutions of Plateau’s roblem at infinity on the hyperbolic space H n , independently of their boundary regularity. We also give a simple condition on the second fundamental form that ensures M to have finite density. In particular, we show that minimal submanifolds of H n with finite total curvature have finite density.